Fragmentação socioespacial em Sorocaba: o caso dos residenciais Carandá e Altos do Ipanema - Carvalho, Gabriel Esmeraldino de (2024)
The process of socio-spatial fragmentation was theorized as an element in the production and consumption of urban space in metropolises. However, this process has also been recorded in medium-sized cities. In this context, the city of Sorocaba is inserted, an important city in the interior of São Paulo whose recent expansion of its urban area and its accelerated growth have registered characteristic elements of socio-spatial fragmentation. In the municipality, there is a growth in closed subdivisions, self-segregated spaces, and in peripheral areas, spaces segregated by imposition. The focus given is on the case study of the Carandá and Altos do Ipanema subdivisions, which are sets of buildings resulting from public housing policies, but built in remote areas, difficult to access, with no basic shops and dependent on a network of Public transport is still lacking and focused on the central region of the city, which makes access to other locations difficult. The analysis methodology is based on interviews with local residents, since the analysis of everyday life is seen as the main element of understanding the lived space and the consequences of socio-spatial fragmentation. Therefore, elements related to consumption, leisure and mobility in the daily lives of the interviewees are investigated.